A tale of two fighters: images of child soldiers in Jewish and African child soldier narratives. Issue 1 (18th March 2022) - Adesola, Ademola
Abstract: In this essay I examine the representations of child soldiers in Yuri Suhl's Uncle Misha's Partisans and Emmanuel Dongala's Johnny Mad Dog . While Suhl's novel recreates the historical fact of Jewish children's involvement in the organized group of resistance fighters – called the Jewish Partisans – during the Second World War and in that sense serves to recreate the history of Jewish child soldiering, Dongala's narrative portrays a conflict in which children are instrumentalized as soldiers in a war propelled by mere avarice, the fighters as ideologically barren, and the children involved as mainly innocent victims of adults' myopia. In comparatively examining these two narratives, I argue that, whereas Suhl offers a positive portraiture of Jewish child soldiers as patriotic beings with agency and voice and constructs a far more nuanced perspective of childhood innocence, Dongala in his own work represents African child soldiers in familiarly negative light.